Is physician location sensitive to changes in patients' financial responsibility? - Marion Aouad (Journal of Applied Economics, 2022)
This study examines how changes to patients' financial responsibility affect physicians' behavior. This is achieved by examining a health insurance reform that changes patients' relative financial responsibilities for a medical service that can be received at one of two locations. In particular, this study examines how physicians' treatment location decisions change after the reform. This study finds that physicians who previously work across the two locations are increasingly observed working at the location that becomes cheaper for patients. Thus, physicians' responsiveness to new policies may be an important lever by which certain demand-side health insurance reforms successfully operate.
Keywords: 330; health insurance; insurance design; insurance reform; Physician agency